2005
DOI: 10.1016/j.aquaculture.2005.03.046
|View full text |Cite
|
Sign up to set email alerts
|

Relative importance of family, site, and field placement timing on survival, growth, and yield of hatchery-produced Pacific oyster spat (Crassostrea gigas)

Abstract: Summer mortality has been reported in the Pacific oyster, Crassostrea gigas, for many years in different parts of the world. The causes of this phenomenon are complex. The multidisciplinary program "MOREST", coordinated by IFREMER, was initiated to understand the causes of summer mortality of Crassostrea gigas juveniles in France and to reduce its impact on oyster production. Within this program, three successive groups of bi-parental families were bred in a hatchery in 2001 and placed in the field during summ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
104
2
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 124 publications
(114 citation statements)
references
References 35 publications
(40 reference statements)
7
104
2
1
Order By: Relevance
“…The causes of the summer mortality phenomenon are complex and depend notably on environmental factors that are impossible to control in field experiments. As heavy mortality was observed in some of our families in each set, we concluded that environmental conditions were conducive to summer mortality for each of our three successive sets (Dégremont et al, 2005a).…”
Section: Discussionmentioning
confidence: 65%
See 4 more Smart Citations
“…The causes of the summer mortality phenomenon are complex and depend notably on environmental factors that are impossible to control in field experiments. As heavy mortality was observed in some of our families in each set, we concluded that environmental conditions were conducive to summer mortality for each of our three successive sets (Dégremont et al, 2005a).…”
Section: Discussionmentioning
confidence: 65%
“…The importance of field placement timing (i.e. differences between sets) on the studied traits in this experiment was previously discussed by Dégremont et al (2005a).…”
Section: Grow-out and Sampling Protocolmentioning
confidence: 81%
See 3 more Smart Citations